Pengaruh Responsibilitas dan Sikap Kerja Terhadap Kualitas Pelayanan di Kelurahan Tengah Kecamatan Cibinong Kabupaten Bogor - A.H. Rahadian; Bambang Rusantono (Institut Ilmu Sosial dan Manajemen STIAMI, 2015)
The problem that made the object of research is the phenomenon of the Quality of Service in Tengah Sub-District at Cibinong District in Bogor Regency is not optimal. The purpose of this study is that analyze the magnitude Influence Responsibility and Work Attitude toward the Quality of Service in Tengah Sub-District at Cibinong District in Bogor Regency.This study uses a quantitative explanatory to saw how much influence X1 and X2 to Y by partial and multiple. Population in this research service recipient in Tengah Sub-District amounted to 1.332 people and sampling by Slovin, the samples are 308 respondents. The research instrument using a Likert scale.Results of the analysis and discussion of the results showed that There is a Significant and Positive Influence of Responsibility toward the Quality of Service in Tengah Sub-District at Cibinong District in Bogor Regency; There is a Significant and Positive Influence of Work Attitude toward the Quality of Service in Tengah Sub-District at Cibinong District in Bogor Regency; and There is a Significant and Positive Influence of Responsibility and Work Attitude together toward the Quality of Service in Tengah Sub-District at Cibinong District in Bogor Regency.